Authenticating criteria in Jesus research and beyond: an interdisciplinary methodology - Burr, Kevin B. (Biblical interpretation series, 2024)
Are the criteria of authenticity of Jesus research idiosyncratic to New Testament studies, vehicles of subjectivity, and fundamentally flawed vestiges of form criticism as some claim today? If so, why do opponents of the criteria-approach still use them? Or, are the criteria the tools of general historiography as others assert? If true, none have adequately demonstrated where and how principles such as multiple attestation, general and historical coherence, dissimilarity and embarrassment feature in general historiographic method - until now. This study analyzes the methods of general historians and Jesus researchers (who favor or oppose the criteria) and demonstrates that, regardless of sub-discipline, authenticating criteria are inherent to the practice of historiography